Penerapan Jurnalisme Bigdata oleh Media Matabandung.Pikiran-Rakyat.com - Ballian Siregar; Yuni Mogot; rantona, Safutra Rantona; Yasundari; Solihin, Olih (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This study examines the application of big data journalism by Matabandung.pikiran-rakyat.com, which utilizes big data technology to enrich and deepen the information presented to readers. The background of this research is driven by the rapid development of digital technology and big data, which offers new opportunities for the media to improve journalism quality. The aim of this research is to understand how Matabandung implements big data in the news production process, as well as the challenges and opportunities faced in this process. This research uses a qualitative approach with a case study method, involving interviews with the editorial leader and loyal readers of Matabandung. The findings show that Matabandung uses big data to enhance news content and ensure that the information presented is more relevant and accurate. However, the management still maintains journalistic ethics, such as verification and source transparency, to uphold the media's credibility amid the increasing competition in digital media. In conclusion, the application of big data journalism at Matabandung has a positive impact on improving journalism quality while prioritizing integrity and the accuracy of the information delivered to the public.